Contingent convertible debt: The impact on equity holders - Delphine Boursicot; Geneviève Gauthier; Farhad Pourkalbassi (Risks, 2019)
Contingent Convertible (CoCo) is a hybrid debt issued by banks with a specific feature forcing its conversion to equity in the event of the bank's financial distress. CoCo carries two major risks: the risk of default, which threatens any type of debt instrument, plus the exclusive risk of mandatory conversion. In this paper, we propose a model to value CoCo debt instruments as a function of the debt ratio. Although the CoCo is a more expensive instrument than traditional debt, its presence in the capital structure lowers the cost of ordinary debt and reduces the total cost of debt. For preliminary equity holders, the presence of CoCo in the bank's capital structure increases the shareholder's aggregate value.
Keywords: 330; credit risk; contingent convertible debt; financial modelling; risk management; financial crisis